Penerapan Total Quality Management dalam Upaya Penjaminan Mutu Internal Sekolah di SD Kristen Satya Wacana Salatiga - Ari - Pujianto (Dinas Pendidikan Kota Salatiga, 2021)
This study aims to know: (1) implementation of internal quality assurance systems in SD Kristen Satya Wacana Salatiga, (2) the barriers in implementing the internal quality assurance systems in SD Kristen Satya Wacana Salatiga, (3) the solution to overcome the barriers in implementing the internal quality assurance systems. This research is a qualitative research. The subjects of this research were the principal, the committee of the school, the internal quality assurance system’s team, the teachers of SD Kristen Satya Wacana Salatiga. Data collection through interviews and document studies. The data validity test is done by source and triangulation technique. The results of this study: (1) the implementation of the internal quality assurance systems in SD Kristen Satya Wacana Salatiga has been doing well (2) the barriers in implementing the internal quality assurance systems, such as: financial condition and infrastructure that can support the improvement of school quality; (3) the effort that has done to overcome the barriers, such as: financing strategies and provide the infrastructures at school.